Assessment of the of effectiveness of internal audit on local government authorities in Tanzania: Case of Mufindi District Council - Anthony, Erick (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as apartial fulfillment of the requirements for the award of the Degree of Master of Science in Accounting and Finance (Msc. A&F) of Mzumbe University